(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Tuberous root explants of Plumbago rosea L. cultured in MS containing 3.5 mg/l BAP showed high frequency of shoot bud regeneration (62.33 ± 0.66; 0.26 ± 0.07 cm) within eight weeks. Subculture of shoot clumps (22.17 ± 0.90 shoots; 0.26 ± 0.07 cm) from the initial clump exhibited extensive rate of shoot multiplication (123.4 ± 1.029 shoots, 0.22 ± 0.01 cm) per each clump and produced a total of 369 shoots in 3.5 mg/l BAP in six weeks. Within two weeks of culture in basal liquid medium, shoot elongation (6.16 ± 0.14 cm) occurred and after three weeks in MS solid medium supplemented with 0.1 mg/l IAA, rooting (14.7 ± 1.2) initiated on the shoots. Ninety six per cent of the rooted plants were established under the shade nethouse with regular watering. Key words: Plumbago rosea, tuberous root, multiple shoots, High frequency D.O.I. 10.3329/ptcb.v20i2.6915 Plant Tissue Cult. & Biotech. 20(2): 203-209, 2010 (December)